Analisis Faktor – Faktor Yang Mempengaruhi Kesiapan Kerja - Dwie Prasasti, Anneke; Yohana, Corry; Lutfia, Annisa (Green Publisher Indonesia, 2023)
This study aims to determine the factors that can affect work readiness. This study measures the variables of work readiness, career guidance, soft skill, work motivation and industrial work practices. This study uses the quantitative method with primary and secondary data collection techniques. The sample uses class XII students at SMKN 20 Jakarta from all majors. Data analysis techniques in this study used IBM SPSS Statistics 25 software and Structural Equation Modeling (SEM) using IBM SPSS AMOS 28 Graphics software. The test result of the hypothesis shows that career guidance affects work readiness. Work motivation affects work readiness. Soft skill affect work motivation. Industrial work practices affect work motivation. Soft skill do not affect work readiness. Industrial work practices do not affect work readiness.